Human Presencing in the Techne of a Contemplative Space - Mary Keator (Dr. Chinmay Pandya, 2020)
In our colleges and universities, spaces are designated and set aside for specific uses. Students eat in dining halls, not in libraries; they sleep in dorm rooms, not in classrooms. The order and cleanliness of these space, along with the hospitality of the people within these spaces impact the overall experience of those within them. As a contemplative practitioner and educator, I am aware of the importance of creating and cultivating a hospitable, ordered, clean, uncluttered space - both externally and internally to support student learning and development. However, during the spring semester of 2017, an unexpected move from a traditional classroom to a contemplative space within the Interfaith Center for my "Writing about Yoga" course highlighted just how impactful a contemplative space is on student learning. As students learned about the yoga tradition, practiced yogic postures, reflected on and integrated what they had learned and practiced, they not only became more present in writing about their subjective experiences, they engaged with each other in intersubjective experiences. In the process, they became more present and began cultivating a community of care.